2017
DOI: 10.1371/journal.pone.0179188
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of inter-operator reproducibility of digital dental and conventional impression techniques

Abstract: PurposeThe aim of this study was to evaluate and compare the inter-operator reproducibility of three-dimensional (3D) images of teeth captured by a digital impression technique to a conventional impression technique in vivo.Materials and methodsTwelve participants with complete natural dentition were included in this study. A digital impression of the mandibular molars of these participants was made by two operators with different levels of clinical experience, 3 or 16 years, using an intra-oral scanner (Lava … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 38 publications
0
31
0
5
Order By: Relevance
“…To prevent any user influence, impression taking was performed by one experienced operator (L.K.) [30]. For better comparison of our results with those in the current literature, an established methodology was used [10].…”
Section: Discussionmentioning
confidence: 99%
“…To prevent any user influence, impression taking was performed by one experienced operator (L.K.) [30]. For better comparison of our results with those in the current literature, an established methodology was used [10].…”
Section: Discussionmentioning
confidence: 99%
“…Accuracy could only be evaluated in comparison, preferably with a gold standard; which is not easy to establish in the oral cavity. Regarding precision, there is only a limited number of in vivo studies in the literature [48][49][50][51].…”
Section: Summary Of Evidencementioning
confidence: 99%
“…25 The user-friendly digital technique may therefore reduce denture quality discrepancy between general dental practitioners, with studies showing increased quality control reported by clinicians and technicians. 25…”
Section: Discussionmentioning
confidence: 99%
“…20 Statistical analysis of an in vivo study concluded the inter-operator reproducibility using digital impression technique may be better compared to the conventional silicone impression technique. 21 The userfriendly digital technique may therefore reduce denture quality discrepancy between general dental practitioners, with studies showing increased quality control reported by clinicians and technicians. 22 A potential service evaluation incorporating more GDPs would provide a greater understanding on GDPs technique on denture fabrication.…”
Section: Discussionmentioning
confidence: 99%